STRATEGI DIGITAL MARKETING DALAM MENINGKATKAN PENJUALAN PADA TOKO DAIVA GOLD DI PASAR MODERN INTERMODA TANGERANG - Salsabilla Hemalia Putri; Senen (Journal of Research and Publication Innovation, 2025)
This study aims to analyze the marketing strategies implemented by Daiva Gold, particularly in utilizing digital marketing to enhance sales and competitiveness in the jewelry industry. Using a qualitative approach, this research conducts in-depth interviews with the owner and customers of Daiva Gold, as well as documentation analysis related to the marketing strategies employed. The findings indicate that Daiva Gold leverages social media platforms such as Instagram and TikTok to build brand awareness and attract customers through engaging content, paid advertisements, and responsive interactions. Additionally, strategies based on customer testimonials and user-generated content further strengthen buyer trust. The SWOT analysis reveals that Daiva Gold's main strengths lie in its high-quality products, excellent customer service, and continuous innovation. However, weaknesses identified include limited product variety and a relatively narrow geographic reach. Opportunities to enhance competitiveness lie in expanding the market both offline and online, as well as optimizing digital services. On the other hand, Daiva Gold faces threats from intense competition in the jewelry industry, rapid changes in trends, and fluctuations in gold prices. This study concludes that the digital marketing strategies applied by Daiva Gold are effective in increasing sales, expanding market reach, and maintaining customer loyalty. However, the company should consider several recommendations, such as diversifying product offerings, improving online service quality, and utilizing data analytics to better understand customer preferences. By doing so, Daiva Gold can maintain its position as a trusted brand and remain competitive in the jewelry market.